Difficult texts: Matthew 28.19-20 - Duffield, Ian K. (Theology, 2017)
Have these two famous verses had too much weight placed upon them? The conclusion to Matthew’s Gospel is used to justify and mandate a vast range of missionary activity, but is this justified by the text? Can it bear the load? A close reading of verses 19-20 suggest that they make sense within Matthew’s Gospel and have a rather different meaning from the popular resort to them as ‘The Great Commission’. The interpretation offered here problematizes totemic ways of reading these verses by seeking to understand them in the light Matthew’s presentation of Jesus and his way as particularly expressed in the Sermon on the Mount.